Authentic Leadership, Komitmen Efektif dan Job Resourcefullness dalam Membentuk Kreatifitas dan Kinerja Pegawai Bank Syariah Indonesia (KCP Perbaungan) - Manurung, Nurlatifah; Yafiz, Muhammad; Anggraini, Tuti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to examine the effect of authentic leadership, effective commitment, and job resourcefullness in shaping employee creativity and performance. The population in this researcher is all employees of Bank Syariah Indonesia (kcp Perbaungan). This research uses quantitative methods, the sample taken in this study was 35 respondents using the saturated sample method. The tool used is multiple linear regression with the help of the SPSS program. The results of the t test, the value of t count < t table where -1.199 < 2.03 with sig 0.240, meaning that authentic leadership has no effect in shaping creativity, 3.199 < 2.03 with sig 0.240, meaning authentic leadership has no effect in shaping creativity, 4.416 > 2.03 with sig 0. 000, meaning that effective commitment has a positive effect in shaping creativity, 5,366> 2.03 with sig 0.000, meaning effective commitment has a positive effect on performance, 3,611> 2.03 with sig 0.001, meaning job resourcefullness has a positive effect in shaping creativity, 3,522> 2.03 with sig 0.001, job resoucefullness has a positive effect in shaping performance. Authentic Leadership is an important leadership style for leaders in the Islamic bank industry in Indonesia. Authentic Leadership will increase the affective commitment of employees, and will increase the Job Resourcesullness of subordinates. affective commitment and Job Resourcesullness will shape employee creativity and performance.